Representation (translation. a transdisciplinary journal, 2022)
Translation studies in China is best understood in the context of the cultural politics of the time. Many debates about translation are in fact debates about the perennial problem of China’s cultural relationship with the world. In its most recent form, the debate is about whether the ‘influx’ of foreign translation theories and the wholesale acceptance of these theories has resulted in a loss of identity for Chinese translation studies.